Pengaruh Status Kebersihan Gigi dan Mulut (OHI-S) pada Lansia yang Menggunakan Gigi Tiruan Sebagian Lepasan Berdasarkan Tingkat Pendidikan - Merdekawati, Putri Dewi; Sugiatno, Erwan (Universitas Muhammadiyah Yogyakarta, 2008)
The aim of this research is to know the inï¬‚uence of oral hygiene status (OHI-S) of elderly people wear removable partial denture base on education level. Removable partial denture is denture to replace one or more tooth, but it is not replace all of the tooth and it surrounds tissue and supported by tooth and the tissue under it, and it can overhaul to the mouth of the user: Data analysis of this research by using chi-square with 3 0 sample elderly people wear removable partial denture which is divided 10 elderly people graduated from base education level, l 0 elderb1 people graduated from middle education level, and 1 0 elder people graduated from high education level on Umbulharjo Yogyakarta. The result of OHI-S examination showed elderly people graduated from base education level have good 1 (3,3%), middle I (33%), bad 8 (26, 7%), elderly people graduated from middle education level have good 2 (6, 7%), middle 3 (10, 0%), bad 5 (16,7%), and elderly people graduated from high education level have good 6 (20,0%), middle 3 (10, 0%), bad I (3,3%). The result showed that p 0,05 and get chi-square count (11,095) chi-square table (9,49) with signiï¬cant 0,026, it means that have the inï¬‚uence of oral hygiene status (OHI-Q of elderbi people wear removable partial denture base on education level.